Industrial training report: Perbadanan Perpustakaan Awam Negeri Perak (PPANPK) / Umi Nadia Jalaludin @ Kamarudin - Jalaludin @ Kamarudin, Umi Nadia (Faculty of Information Management, 2022)
The report aims to provide evidence on practicum industrial training fulfilling the subjects of industrial training (IMC690). The report is apportioned into chapters which are the background of the organization, organization information, industrial training activities, industrial training reflection and conclusion. All chapters are described with activities in the foundation of learning goals, vision, and expectations borne within the organization. The practicum concentrates on practice-oriented based tasks with the vision for the application of knowledge, skills, and experience in Perbadanan Perpustakaan Awam Negeri Perak training. The practicum of a 24-week work placement by working under the supervision of an experienced information professional, in the achievement of contribution to the activities of the workplace and meet the same demands of work production and responsibility expected by the organization of its regular employees. Special project of RDA Merging/Conversion Record are conducted with new dynamic skills applied. It is a learning experience in adapting the managerial and technical skills in a library and information environment, to demonstrate experiences in any specific area of interest, evaluate the specific area of interest from a managerial perspective, and display a professional commitment to ethical practice at the industrial workplace.